2017
DOI: 10.1038/leu.2017.159
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1b/2b multicenter study of oral panobinostat plus azacitidine in adults with MDS, CMML or AML with ⩽30% blasts

Abstract: Treatment with azacitidine (AZA), a demethylating agent, prolonged overall survival (OS) vs conventional care in patients with higher-risk myelodysplastic syndromes (MDS). As median survival with monotherapy is <2 years, novel agents are needed to improve outcomes. This phase 1b/2b trial (n=113) was designed to determine the maximum tolerated dose (MTD) or recommended phase 2 dose (RP2D) of panobinostat (PAN)+AZA (phase 1b) and evaluate the early efficacy and safety of PAN+AZA vs AZA monotherapy (phase 2b) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…62 However, a phase 2b trial randomizing 82 patients with MDS, CML, or AML to panobinostat and azacitidine or azacitidine alone found that patients derived no benefit from the addition of panobinostat. 63 No differences were observed in response rates or OS; in fact, patients receiving the combination experienced more grade $3 AEs (97.4% vs 81%) and on-treatment deaths (13.2% vs 4.8%) than did those receiving azacitidine alone.…”
Section: Histone Deacetylase Inhibitorsmentioning
confidence: 86%
“…62 However, a phase 2b trial randomizing 82 patients with MDS, CML, or AML to panobinostat and azacitidine or azacitidine alone found that patients derived no benefit from the addition of panobinostat. 63 No differences were observed in response rates or OS; in fact, patients receiving the combination experienced more grade $3 AEs (97.4% vs 81%) and on-treatment deaths (13.2% vs 4.8%) than did those receiving azacitidine alone.…”
Section: Histone Deacetylase Inhibitorsmentioning
confidence: 86%
“…However, the non-selectivity of the HDAC inhibitors leads to obvious toxicity and side effects and limits the clinical application [92, 93]. …”
Section: Hdac6 Inhibitorsmentioning
confidence: 99%
“…16 19,20 Despite sound rationale for the combining standard of care hypomethylating agents with histone deacetylase inhibitors such as vorinostat, entinostat, or panobinostat to enhance gene silencing, no added benefit has been detected to date. [21][22][23][24][25][26] First associated with myeloid neoplasms in 2009 by Delhommeau et al and since noted to have incidence of about 22% in MDS (and up to 60% in CMML), the most prevalent recurring mutations with regards to DNA methylation in MDS are that of TET2, which catalyzes the CpG demethylation of methylcytosine to 5-hydroxymeth ylcytosine. 5,13,18,27,28 One study noted that 26% of cases of TET2mutated MDS possess a second TET2 mutation which supports the notion that biallelic functional TET2 loss likely contributes to MDS pathogenesis.…”
Section: A Mutated Spliceosomementioning
confidence: 99%